2020
DOI: 10.1111/jgs.16392
|View full text |Cite
|
Sign up to set email alerts
|

Wish to Die in Older Patients: Development and Validation of Two Assessment Instruments

Abstract: OBJECTIVES The wish to die may be different in geriatric patients than in younger terminally ill patients. This study aimed to develop and validate instruments for assessing the wish to die in geriatric patients. DESIGN Cross‐sectional study. SETTING Geriatric rehabilitation unit of a university hospital. PARTICIPANTS Patients (N = 101) aged 65 years or older with a Mini‐Mental State Examination score of 20 or higher, admitted consecutively over a 5‐month period. MEASUREMENTS The Schedule of Attitudes Toward H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…This variability between WTD instruments has been noted previously [30]. The authors of a previous validation article found lower variation between the SAHD-senior and the CADO [3], perhaps because of the non-acute context, where patients present with more chronic symptomatology. Overall, our results suggest that WTD prevalence is low but highly relevant for clinical practice in an acute care setting, and that the two WTD instruments do not capture the WTD in the same individuals.…”
Section: Prevalence Of the Wish To Diesupporting
confidence: 63%
See 4 more Smart Citations
“…This variability between WTD instruments has been noted previously [30]. The authors of a previous validation article found lower variation between the SAHD-senior and the CADO [3], perhaps because of the non-acute context, where patients present with more chronic symptomatology. Overall, our results suggest that WTD prevalence is low but highly relevant for clinical practice in an acute care setting, and that the two WTD instruments do not capture the WTD in the same individuals.…”
Section: Prevalence Of the Wish To Diesupporting
confidence: 63%
“…As WTD instruments vary [3], we assessed WTD using two validated instruments to ensure that the construct was adequately measured in this large sample. We considered patients to show a WTD if responses on either or both instruments were positive.…”
Section: Wish To Diementioning
confidence: 99%
See 3 more Smart Citations